28. INITIAL ASSESSMENT OF THE EFFECTIVENESS OF APPLYING THE AIDET STANDARD COMMUNICATION MODEL AT QUAN SON DISTRICT GENERAL HOSPITAL, THANH HOA PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Initial assessment of the effectiveness of knowledge and attitude change after applying the AIDET standard communication model at Quan Son District General Hospital, Thanh Hoa Province in 2024.Subject and method: Intervention study, comparing and evaluating before and after intervention. The subjects are healthcare workers at Quan Son District General Hospital, Thanh Hoa Province (1/2024 - 11/2024).Results: After the training, healthcare workers had a high level of knowledge, attitude and intention to apply the AIDET model, specifically: The rate of knowledge reaching the AIDET criteria before the training was 47.7%, increasing to 84.6% after the training (p
Keywords: AIDET; communication; healthcare workers